2014
DOI: 10.1371/annotation/cc98ac47-e02a-400f-9213-05352b23a144
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Flavonoid Rutin Increases Thyroid Iodide Uptake in Rats

Abstract: Thyroid iodide uptake through the sodium-iodide symporter (NIS) is not only an essential step for thyroid hormones biosynthesis, but also fundamental for the diagnosis and treatment of different thyroid diseases. However, part of patients with thyroid cancer is refractory to radioiodine therapy, due to reduced ability to uptake iodide, which greatly reduces the chances of survival. Therefore, compounds able to increase thyroid iodide uptake are of great interest. It has been shown that some flavonoids are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The best performance was obtained in the T3 transaction compared to the rest of the transactions. The reason may be attributed to the role of the active compounds in aloe vera oil, the most important of which is the aloin and saponin, which may lead to increased absorption and readiness of elements within the gut [19], or due to the direct effect on the microorganisms inside the gut, which increases the beneficial bacteria at the expense of the harmful [20], which improves the health of the digestive system, and enhances the secretion of digestive enzymes, which benefits more from the amount of feed intake [21], or it may be attributed to aloe vera oil acting as an antioxidant and bacterial inhibitor, aAs well as the presence of flavonoids in increasing some important elements inside the body [22].…”
Section: Resultsmentioning
confidence: 99%
“…The best performance was obtained in the T3 transaction compared to the rest of the transactions. The reason may be attributed to the role of the active compounds in aloe vera oil, the most important of which is the aloin and saponin, which may lead to increased absorption and readiness of elements within the gut [19], or due to the direct effect on the microorganisms inside the gut, which increases the beneficial bacteria at the expense of the harmful [20], which improves the health of the digestive system, and enhances the secretion of digestive enzymes, which benefits more from the amount of feed intake [21], or it may be attributed to aloe vera oil acting as an antioxidant and bacterial inhibitor, aAs well as the presence of flavonoids in increasing some important elements inside the body [22].…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are phenolic polyhydroxy compounds which are not only able to modulate NIS and thyroperoxidase as a key enzyme in the biosynthesis of thyroid hormones but also have anti-proliferative properties. Goncalves et al [13] showed that the consumption of flavonoid rutin led to a decrease in serum T 3 and T 4 , without changes in TSH and could significantly increase hypothalamic, pituitary and brown adipose tissue type 2 deiodinase. This could also end in a decrease in the activities of liver type 1 deiodinase.…”
Section: Discussionmentioning
confidence: 99%
“…Other miscellaneous studies have highlighted the potential of other agents as candidates for redifferentiation strategy (Marsee et al 2004, Goncalves et al 2013, Bauriaud-Mallet et al 2019, Chai et al 2019, Vella et al 2019.…”
Section: Other Potential Strategiesmentioning
confidence: 99%